Sosialisasi Koperasi oleh Mahasiswa KKN-T dalam Upaya Penguatan Kelembagaan Ekonomi Masyarakat di Dusun Tambak - Nisa, khoirun; Anjani, Revi Putri Dwi; Pahlevi, Firdha Maudiyah; Marliantari, Sulistina; Putri Asrudi, Lutfia Ardita Mayra; Alfan Biroli; Junaedi, Abdus Salam; Zainuri, Muhammad (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
Village Unit Cooperatives (KUDs) have an important role in supporting the rural economy, but their institutional sustainability is often hampered by a lack of community understanding and weak cooperative management. This article aims to analyse KUD socialisation activities conducted by students of Trunojoyo University Madura's Thematic Community Service Program (KKN-T) as an effort to manage and strengthen cooperative institutions. This activity involved education on cooperative principles, training on administrative management, and providing strategic assistance to village communities. The implementation methods included a participatory approach through group discussions, simulations, and ongoing monitoring. The results showed that the socialisation successfully increased the community's understanding of the role of cooperatives, improved the administrative system, and increased community participation in cooperative management. In addition, KKN-T students acted as facilitators who bridged the needs of the community with the potential of the cooperative. In conclusion, cooperative socialisation activities by KKN-T students of Trunojoyo University Madura are a strategic step in strengthening cooperative institutions at the village level. These findings can serve as the basis for developing a cooperative empowerment model based on collaboration between universities and communities.